Comparative transcriptomics of the irradiated melon fly (Zeugodacus cucurbitae) reveal key developmental genes - Ahmad, Shakil; Jamil, Momana; Jaworski, Coline C.; Luo, Yanping (Frontiers in Physiology, 2023)
Irradiation can be used as an insect pest management technique to reduce post-harvest yield losses. It causes major physiological changes, impairing insect development and leading to mortality. This technique is used to control the melon fly Zeugodacus cucurbitae, a major pest of Cucurbitaceae in Asia. Here, we applied irradiation to melon fly eggs, and the larvae emerged from irradiated eggs were used to conduct comparative transcriptomics and thereby identify key genes involved in the development and survival. We found 561 upregulated and 532 downregulated genes in irradiated flies compared to non-irradiated flies. We also observed abnormal small-body phenotypes in irradiated flies. By screening the 532 downregulated genes, we selected eight candidate genes putatively involved in development based in described functions in public databases and in the literature. We first established the expression profile of each candidate gene. Using RNA interference (RNAi), we individually knocked down each gene in third instar larvae and measured the effects on development. The knockdown of ImpE2 ecdysone-inducible gene controlling life stage transitions–led to major body size reductions in both pupae and adults. The knockdown of the tyrosine-protein kinase-like tok (Tpk-tok) caused severe body damage to larvae, characterized by swollen and black body parts. Adults subject to knockdown of the eclosion hormone (Eh_1) failed to shed their old cuticle which remained attached to their bodies. However, no obvious developmental defects were observed following the knockdown of the heat shock protein 67B1-like (Hsp67), the insulin receptor (Insr), the serine/threonine-protein kinase Nek4 (Nek4), the tyrosine-protein kinase transmembrane receptor Ror (Ror_1) and the probable insulin-like peptide 1 (Insp_1). We argue that irradiation can be successfully used not only as a pest management technique but also for the screening of essential developmental genes in insects via comparative transcriptomics. Our results demonstrate that ImpE2 and Eh_1 are essential for the development of melon fly and could therefore be promising candidates for the development of RNAi-based pest control strategies.